Forensic podiatry principles and methods - DiMaggio, John A. (Humana Press, 2011)
The human foot is a complex body part composed of fifty-two bones, which is twenty-five percent of all the bones in the body. Nonetheless, the foot is often viewed by the public and doctors as a 'minor' body part. Similarly, the importance of pedal evidence in crime investigation has also long been undervalued, but as footwear evidence has become more commonly used in forensic situations, so has pedal evidence, which is why this seminal work is so important: it is the first textbook ever dedicated to forensic podiatry. "Forensic Podiatry" is an international compilation of current pr.